Assessment of the healthcare managerial skills offered by the Italian post-graduate schools of public health - Furmenti, M. F.; Barbara, A.; Voglino, G.; Beltramello, C. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The Italian National Health Service (Servizio Sanitario Nazionale, SSN) is facing relevant challenges due to decreased financing and increased healthcare costs (1). In this complex framework, most of the Italian Medical Doctors, after obtaining their Specialization degree in Public Health, develop their careers in organizational and managerial roles in public and private health organizations, i.e. hospitals, local health units, health districts or national and international agencies (1, 2). Public health technical competencies, in particular policy and management, are of crucial importance to develop, run and support healthcare services. However, some gaps exist between current public health needs and the extent to which Public Health Residents are trained in the above fields (3, 4). Study design. The study is a cross-sectional cognitive survey carried out through a questionnaire sent by e-mail to Residents and Directors of the Italian Schools of Public Health, from May to November 2018. The questionnaire was sent only to the accredited Schools which had all four years of the course running. Methods. The questionnaire investigated 35 managerial topics divided into 4 macro-areas. It was sent to both Directors of the SPHs and the Residents of 32 Schools. The latter were asked to provide a single collective answer per School. Respondents could assign a score from 1 (topic not addressed at all) to 4 (topic addressed extensively and linked to other related topics) to each item, also taking into account the skills acquired through internships, seminars, etc. that involved all the Residents. Results. Answers were received from the Residents of 30/32 (93.8%) SPHs and from 15/32 (46.9%) of the Directors. Scores given by the Directors were higher than the ones of the Residents for every topic, and for 17 out of 35 items (48.6%) a statistically significant difference has been obtained. In the overall score of 3 macro-areas out of 4 (General issues, Managerial tools and macro-organisational Models) there are statistically significant differences. In Soft skills macro-area, the single scores of all topics are generally low for both Directors and Residents. Conclusion. The study shows that the Residents declare a strong need for training improvement in the field pf healthcare organization and management: the median score is equal to or greater than 3 (topic addressed extensively) in only a few answers. The comparison between Directors’ and Residents’ scores highlights a different perception of the training offered in these areas. The study results could be pivotal for the improvement of the managerial skills provided to the Residents in Public Health of the Country.